The Impact of Sharia Insurance on Systematic Risk Protection and Reducing Poverty Levels: A Critical Analysis - Muhammad Habib Yuldihansyah; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the impact of Sharia Insurance on systematic risk protection and reducing poverty levels with a critical analysis approach. Sharia Insurance, as a form of insurance based on Islamic sharia principles, has the main aim of providing financial protection that is in line with Islamic values. This research investigates the impact of Sharia Insurance in the context of systematic risk protection and poverty reduction efforts. Through a qualitative and literature review approach, this research reveals the success of Sharia Insurance in providing effective protection against economic risks. Sharia principles, such as fair risk sharing, prove to be the key foundation for this success. With effective risk transfer and fairness in managing premium funds, Sharia Insurance also has a positive impact on people's financial stability. The research also identified a number of challenges, including poor public understanding and regulatory barriers. As a solution, research recommends intensive educational programs, cooperation of interested parties, and regulatory updates. The implications of this research highlight the need for increasing public understanding, updating regulations, and developing innovative products to support the sustainable growth of Sharia Insurance.